2013
DOI: 10.1038/ismej.2013.40
|View full text |Cite
|
Sign up to set email alerts
|

Acetate oxidation by syntrophic association between Geobacter sulfurreducens and a hydrogen-utilizing exoelectrogen

Abstract: Anodic microbial communities in acetate-fed microbial fuel cells (MFCs) were analyzed using stableisotope probing of 16S rRNA genes followed by denaturing gradient gel electrophoresis. The results revealed that Geobacter sulfurreducens and Hydrogenophaga sp. predominated in the anodic biofilm. Although the predominance of Geobacter sp. as acetoclastic exoelectrogens in acetate-fed MFC systems has been often reported, the ecophysiological role of Hydrogenophaga sp. is unknown. Therefore, we isolated and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…For the co-culture to be syntrophic, it would require that G. sulfurreducens ceases to be an electrogen, or more precisely ceases to be able to use electrodes as electron acceptor. The data put forward by Kimura and Okabe (2013) provide no evidence that this indeed the case, though they do indicate that G. sulfurreducens PCA benefits from the presence of Hydrogenophaga sp. strain AR20.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…For the co-culture to be syntrophic, it would require that G. sulfurreducens ceases to be an electrogen, or more precisely ceases to be able to use electrodes as electron acceptor. The data put forward by Kimura and Okabe (2013) provide no evidence that this indeed the case, though they do indicate that G. sulfurreducens PCA benefits from the presence of Hydrogenophaga sp. strain AR20.…”
mentioning
confidence: 90%
“…That is, until recently. Earlier this year Kimura and Okabe (2013) reported that Geobacter sulfurreducens PCA can oxidize acetate in what the authors labelled 'a syntrophic cooperation' with Hydrogenophaga sp. strain AR20 in conjunction with an electrode as the final electron acceptor.…”
mentioning
confidence: 99%
“…29,30 However, it was reported that H. intermedia and H. atypica are unable to grow chemolithoautotrophically using hydrogen gas, and only a few organic compounds can be used as sole carbon sources.…”
Section: Growth Characterizationmentioning
confidence: 99%
“…Organic matter can be used as a renewable resource to generate electrons and protons via electrochemically active bacteria in MFCs [4][5][6]. Protons are released into solution and electrons are produced at the anode; subsequently, at the interface of the cathode, electrons pass through the outer circuit before they can reach the cathode and combine with electron acceptors [7,8].…”
Section: Introductionmentioning
confidence: 99%